2016
DOI: 10.1210/en.2016-1577
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Modifications of Lipid-Activated Nuclear Receptors: Focus on Metabolism

Abstract: Posttranslational modifications (PTMs) occur to nearly all proteins, are catalyzed by specific enzymes, and are subjected to tight regulation. They have been shown to be a powerful means by which the function of proteins can be modified, resulting in diverse effects. Technological advances such as the increased sensitivity of mass spectrometry–based techniques and availability of mutant animal models have enhanced our understanding of the complexities of their regulation and the effect they have on protein fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 108 publications
0
32
0
Order By: Relevance
“…We now propose that changes in LXRα phosphorylation play a crucial role in these transitional stages of the disease. understanding of how these modifications impact on metabolic diseases is scarce (7). Notably, the physiological consequences of LXRα phosphorylation, sumoylation and acetylation have only been studied in vitro or non-specifically in animal models by pharmacologically or genetically altering the enzymes enhancing or inhibiting these modifications (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We now propose that changes in LXRα phosphorylation play a crucial role in these transitional stages of the disease. understanding of how these modifications impact on metabolic diseases is scarce (7). Notably, the physiological consequences of LXRα phosphorylation, sumoylation and acetylation have only been studied in vitro or non-specifically in animal models by pharmacologically or genetically altering the enzymes enhancing or inhibiting these modifications (7).…”
Section: Discussionmentioning
confidence: 99%
“…understanding of how these modifications impact on metabolic diseases is scarce (7). Notably, the physiological consequences of LXRα phosphorylation, sumoylation and acetylation have only been studied in vitro or non-specifically in animal models by pharmacologically or genetically altering the enzymes enhancing or inhibiting these modifications (7). To directly address the impact of LXRα phosphorylation on NAFLD progression, we generated a novel mouse model harbouring an S196A mutation that disrupts LXRα phosphorylation at Ser196.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver X receptors (LXRs) are ligand activated transcription factors that play vital roles in cholesterol homeostasis (3) and inflammation (4). LXRs are expressed as two isotypes; LXRα and LXRβ, which display 78% sequence homology, yet vary in their tissue expression and regulation (5). Both LXRs are endogenously activated by oxidized metabolites of cholesterol (6) and…”
Section: Introductionmentioning
confidence: 99%
“…LXRα transcriptional activity can be modulated by several posttranslational modifications (5) including phosphorylation at serine (S) 198 in the human sequence, corresponding to S196 in the mouse orthologue. We have demonstrated that modulation of LXRα phosphorylation significantly modifies its target gene repertoire in macrophage cell lines overexpressing the receptor, thereby altering pathways known to be relevant to the development of atherosclerosis (13,14).…”
Section: Introductionmentioning
confidence: 99%